Assessment of Oral Hygiene Maintenance among Young Adults (Medical Forum Monthly, 2020)
Objective: Oral health is essential for general health of the individuals, poor health is related to significant morbidity and it affects the quality of life of the affected person. The objective of the present study was to assess the oral hygiene practices among students of different institutions of Karachi city.Study Design: Cross Sectional study.Place and Duration of Study: This study was conducted at different educational institutions of Karachi and Hyderabad (Bahria University of Medical and Dental College University, University Dental College, Hyderabad) from January 2019 to June 2019.Materials and Methods: It was conducted among 500 subjects who were randomly selected from the different educational institutions of Karachi and Hyderabad. A questionnaire was administered to determine the oral health knowledge and practice in 500 samples from January to June, 2019. The data was analyzed on statistical package for the social sciences (SPSS), version 23.Results: The present study findings showed that majority of the male students 338 (98.5%) used tooth brush as a cleaning aid followed by miswak 4(1.2%) and Manjan 1(0.3%). Medium bristled tooth brush was more widely used among females as compared to males with a p-value 0.004. The change of tooth brush was observed within 1-3 months with significance of <0.05 p-value.Conclusion: In this study potential for the improvement in the oral health status and interest in taking modern oral hygiene maintenance measures among students was found significant. However, much emphasize must be taken on a larger scale to implement these measures for general young population.